2012
DOI: 10.1007/s10825-012-0396-9
|View full text |Cite
|
Sign up to set email alerts
|

Analog and RF performance investigation of cylindrical surrounding-gate MOSFET with an analytical pseudo-2D model

Abstract: We report a systematic, quantitative investigation of analog and RF performance of cylindrical surroundinggate (SRG) silicon MOSFET. To derive the model, a pseudotwo-dimensional (2-D) approach applying Gauss's law in the channel region is extended for the cylindrical SRG MOSFET. Based on surface potential approach, expressions of drain current and differential capacitances are obtained analytically. Analog/RF figures of merit of SRG MOSFET are studied, including transconductance efficiency g m /I d , intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…A parameter generally described when comparing transistors for RF applications is the cut-off frequency, f T [31,32]. f T is a specification for high-speed digital applications (speed and high swing) and can be defined as follow:…”
Section: Rf Performance Metrics Inquisitionmentioning
confidence: 99%
“…A parameter generally described when comparing transistors for RF applications is the cut-off frequency, f T [31,32]. f T is a specification for high-speed digital applications (speed and high swing) and can be defined as follow:…”
Section: Rf Performance Metrics Inquisitionmentioning
confidence: 99%
“…The results are then substituted in above equations where current is expressed in terms of carrier density, which is continuous from subthreshold to strong inversion region. The transconductance g m is expressed as [11] …”
Section: Inversion Layer Centroidmentioning
confidence: 99%
“…where l 0 is electron mobility with its value taken to be 677 cm 2 /V s, the values of the parameters S = 350, N ref = 3 脗 10 22 m 脌3 and high field saturation velocity V sat = 10 7 cm/s is considered as given in [11] The expressions for the terminal charges were derived using the Ward-Dutton linear charge partition method [11].…”
Section: Inversion Layer Centroidmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the radius of the nanowire can readily be reduced to a few nanometres in size that limits the scaling of conventional MOSFET and also because of their adoptability for high-density integration including that of 3D [7,8]. It was also found that gate-all-around (GAA) silicon nanowire transistors (SiNWTs) have cut-off frequency larger than that of planar Si MOSFET [9][10][11]. However, as with many novel device architectures, the SiNW MOSFET has problems of its own.…”
Section: Introductionmentioning
confidence: 99%